Pengaruh Pelatihan Dan Motivasi Kerja Terhadap Produktivitas Kerja Karyawan Magang Bakti Di PT Bank Central Asia Tbk KCU Harapan Indah Bekasi - Niken Salsabilla; Tungga Buana Irfana; Supriyanto Supriyanto; Djuni Thamrin; Matdio Siahaan (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to determine and analyze the effect of training and work motivation on the productivity of apprentice employees at PT. Bank Central Asia Tbk. KCU Harapan Indah Bekasi. This type of research is quantitative and the data analysis used is the classical assumption test and multiple linear regression analysis, to test and prove the research hypothesis using the SPSS version 26 application. Partially, the training variable affects employee work productivity with a t-count> t-table value. Based on the test results and data analysis, the partial test calculation results show a value of 4.496 (t-count) > 2.022 (t-table) with a significance value of 0.000 <0.05. Partially, the work motivation variable has an influence on employee productivity with a t-count> t-table value. Based on the test results and data analysis, the partial count results obtained show a value of 2.491 (t-count) > 2.022 (t-table) with a significance value of 0.017 < 0.05. Meanwhile, based on the simultaneous test results obtained from this study from the training and work motivation variables, a value of 10.392 (f count)> 3.24 (f table) has been obtained.